1992
DOI: 10.1017/s0022112092002209
|View full text |Cite
|
Sign up to set email alerts
|

An advanced experimental investigation of quasi-two-dimensional shear flow

Abstract: Forced shear flows in a thin layer of an incompressible viscous fluid are studied experimentally. Streak photographs are used to obtain the stream function of vortical flow patterns arising after the primary shear flow loses stability. Various flow characteristics are determined and results are compared to the stability theory of quasi-two-dimensional flows. The applicability of the quasi-two-dimensional approximation is directly verified and the possibility of reconstruction of the driving force from the seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 9 publications
1
42
0
Order By: Relevance
“…19 As yet, it is not completely clear whether this approximation is valid in general for shallow water flows. It is worthwhile to note that it was shown by Dolzhanskii et al 14,15 that the 2D hydrodynamic equation with Rayleigh friction correctly describes the stability of shear flows in thin layers of homogeneous fluid.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…19 As yet, it is not completely clear whether this approximation is valid in general for shallow water flows. It is worthwhile to note that it was shown by Dolzhanskii et al 14,15 that the 2D hydrodynamic equation with Rayleigh friction correctly describes the stability of shear flows in thin layers of homogeneous fluid.…”
Section: Introductionmentioning
confidence: 88%
“…[8][9][10] Besides the experiments on soap films, it is also possible to study Q2D flows in a thin layer of fluid inside a container, for example, the experiments on vortex interactions performed by Antonova et al 11 and the experiments on freely decaying Q2D turbulence by Tabeling et al 12 In the latter experiment, but also in several other studies of this type, the flow is forced electromagnetically. Other examples are the experiments on the interaction of allocated vortices performed by Danilov et al 13 and the experimental study of Q2D shear flows by Dolzhan-skii et al 14,15 In the experimental studies on thin-layer flows of this type, usually a single layer of fluid is used. Recently, in the experiments of Paret and Tabeling, 16 a system of saltstratified fluid layers was used.…”
Section: Introductionmentioning
confidence: 99%
“…The forcing system is an adaptation of a well-known system commonly used for shallow-flow experiments, introduced by Sommeria (1986), and independently further developed by Tabeling et al (1991) and Dolzhanskii et al (1992). The system consists of a container filled with a layer of mercury (Sommeria, 1986) or NaCl solution (Tabeling et al, 1991, Dolzhanskii et al, 1992, and a constant current density field parallel to the bottom of the container.…”
Section: Electromagnetic Forcingmentioning
confidence: 99%
“…The system consists of a container filled with a layer of mercury (Sommeria, 1986) or NaCl solution (Tabeling et al, 1991, Dolzhanskii et al, 1992, and a constant current density field parallel to the bottom of the container. The current is provided by a power supply, and it is homogeneously distributed through the fluid via two electrodes placed along two opposite sides of the domain.…”
Section: Electromagnetic Forcingmentioning
confidence: 99%
“…Such vertical dependence of the horizontal flow field is consistent with the fact that the flow is dominated by bottom drag as will become clear later. From previous studies, 8,9 it was concluded that such flows relax quickly to a Poiseuille flow, which is usually modeled by a Rayleigh bottom friction term 10,11 as implied by (3) and (4) when substituted in (1). The pressure distribution inside the fluid layer is dictated by the following Poisson equation that results from taking the divergence of (1):…”
Section: Quasi-linear Theory Of Secondary Motion In Q2d Shallow Fmentioning
confidence: 99%